Effect of the number of unhealthy lifestyles in middle-aged and elderly people on hypertension and the first occurrence of ischemic stroke after the disease - Zhu, Xiaopeng; Zhang, Fang; Luo, Zhongyan; Liu, He; Lai, Xia; Hu, Xiaotong; Xie, Qian; Gao, Xia; Long, Yan (Frontiers in Cardiovascular Medicine, 2023)
Background To determine the relationship between the number of controllable unhealthy lifestyles on the risk of the first occurrence of ischemic stroke after the disease in middle-aged and elderly people in the community, and to provide data support and basis for community physicians to guide hypertensive patients to control modifiable risk factors to prevent the first occurrence of ischemic stroke. Methods The relationship between the number of unhealthy lifestyles and the risk of hypertension was analyzed by binary logistic regression in 584 subjects using a medical record control study. A retrospective cohort study of 629 hypertensive patients was used to analyze the relationship between the number of unhealthy lifestyles and the risk of the first occurrence of ischemic stroke within 5 years of developing hypertensive disease using Cox proportional risk regression models. Results Logistic regression model analysis showed that taking an unhealthy lifestyle as a reference, the OR (95% CI) values of, 2, 3, 4 and 5 unhealthy lifestyle were 4.050 (2.595–6.324), 4 (2.251–7.108), 9.297 (3.81–22.686), and 16.806 (4.388–64.365), respectively. Cox Proportional risk regression model analysis showed that the risk of ischemic stroke within 5 years after developing hypertension was referenced to 5 unhealthy lifestyles, and the HR (95% CI) for 3, 2, and 1 unhealthy lifestyle were 0.134 (0.023–0.793), 0.118 (0.025–0.564), and 0.046 (0.008–0.256), respectively. Conclusion The number of controllable unhealthy lifestyles in middle-aged and elderly people was positively associated with the risk of hypertension and first ischemic stroke after hypertension, and there was a dose-effect relationship between them. The risk of hypertension and first ischemic stroke within 5 years after hypertension onset increased with the number of unhealthy lifestyles.